Creative processes and emotions in COVID-19 pandemic - Elisondo, Romina Cecilia (Creativity Studies, 2022)
The objective was to analyse, from the perspective of the participants, creative processes developed in isolation and social distancing by COVID-19 pandemic. The main interest was to study transformations in daily, family and work life, focusing on the creation of new practices and projects. Likewise, it was relevant to study emotions, obstacles and difficulties perceived by the participants. The study was qualitative, the participants (N = 25) were selected by non-probabilistic convenience sampling. All the participants lived in intermediate or small towns in Argentina. Data collection was carried out in September, 2020. Semi-structured interviews and online qualitative research were the data collection instruments. The Atlas.ti 8 program was used for the qualitative analysis of textual and audio-visual data. The results indicated significant modifications in the lives of the participants from isolation and distancing. These changes demand flexibility and adaptability as well as creative processes for generating alternatives and solving problems. In the context of the home, transformations of times, spaces and relationships were observed. Work and leisure activities also were reconfigured. Sadness appeared as the predominant emotion. However, some participants experienced enthusiasm and joy for the new projects. The purpose of this study was to build knowledge that contributes to the design of health promotion project.